PERAN KOMISI PEMILIHAN UMUM DALAM MENSOSIALISASIKAN PEMILIH PEMULA PADA PEMILIHAN KEPALA DAERAH KOTA MEDAN TAHUN 2020: TINJAUAN SIYASAH - Zurnailis, Afriana; Irwansyah, Irwansyah; Lubis, Syaddan Dintara (Hukum tata Negara/Siyasah, 2022)
This study aims to determine the extent of the political participation of young voters in the city of Medan and the role of the General Elections Commission (KPU) in socializing new prospective voters in the 2020 Medan City Pilkada and to find out how Siyasah views political participation in the post-conflict local election. regional election. This research uses the type of empirical juridical legal research. Empirical legal research is a type of legal research that analyzes and examines the work of law in society. The data used in this study come from primary data sources and secondary data sources. Data collection techniques used are by conducting interviews and observations. The data analysis technique used is a qualitative data analysis technique. The results of this study indicate that the participation of first-time voters has increased because the KPU of Medan City has evaluated and conducted socialization well and optimally so as to be able to increase the participation of first-time voters, which was originally only 25.38%. in 2015, now it has increased to 45.80% in 2020. Based on the study of siyasah on political participation in the 2020 regional election for the mayor of Medan, it is in accordance with the concept offered by siyasah at all.